4P delays in project management. Issue 1 (19th February 2018) - Ansah, Richard Hannis; Sorooshian, Shahryar
Abstract : Purpose: As a result of the increasing challenges of time overrun, several companies regularly set up delay assessment procedures for performance improvement and profit maximization. In the construction industry, projects are enormously complicated and involve significant budgets, and therefore optimizing project performance through the root cause analysis should be imperative for every project manager. Typically issues of delays in projects are generally discussed and problematized separately, yet a comprehensive framework for systematic analysis and grouping of delays is rarely contended. The purpose of this paper is to introduce the 4P concept (project related, practices, participants, and procurement) for identifying, analyzing, and classifying delays in the internal environment of the project development process. Design/methodology/approach: The 4P conceptual framework was validated through the synthesis of the existing literature. Findings: Interestingly, despite the increasing concerns about delays in the construction industry, most research on delays are project and/or country specific, thus no consensus about the sources of delays. The application of the proposed concept as a theoretical framework would provide an understanding of the available delay sources, their risks and use for project delay assessment and classification. Research limitations/implications: This study grouped delays based on the shared characteristics and four main sources were identified and analyzed. There may be other sources or factors, yet would be dependent or aspect of the 4P. Practical implications: The study informs project teams to reduce delays in the construction industry. Originality/value: The paper is an application of risk assessment tool to conceptualize delays in the internal project environment.